Perancangan Sistem Absensi Berbasis Internet of Things Menggunakan RFID dan Arduino - Fitriyani Fitriyani; Tia Luthfia Annisa; Debi Irawan; Fauzan Daffa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study discusses the design of an Internet of Things (IoT)-based attendance system using RFID and NodeMCU ESP8266 to support and improve the efficiency of teacher attendance management at MTs Al-Ikhlas Cicalengka. The primary problem motivating this study is the reliance on a conventional manual attendance system, which is highly vulnerable to recording errors (human error), time inefficiencies during daily data recapitulation, and the risk of physical document loss or damage. Therefore, digital transformation is urgently needed. The proposed system integrates several hardware components: RFID RC522 as the identity card reader, NodeMCU ESP8266 as the main controller and internet (Wi-Fi) connector, and a 16x2 LCD as an interactive information display. The attendance data is directly transmitted and stored in a cloud-based Google Spreadsheet. The system was programmed using Arduino IDE to operate automatically. This study utilized a design and prototyping method by testing 10 registered RFID cards belonging to the teachers. The test results demonstrated that all cards were successfully read, and attendance data were accurately stored in Google Spreadsheet with a 100% success rate. The average system response time was recorded at a very fast 2.2 seconds. In conclusion, the implementation of this IoT-based attendance system is proven to be effective in minimizing data manipulation, accelerating the recording process, and generating attendance recapitulations that are more transparent and easily accessible. The contribution of this research is providing a practical, affordable automation system that can serve as a reference model for other secondary educational institutions in digitally transforming their administrative management.